Efeitos de brassinosteroides sobre aspectos fisiológicos em mudas de açaí na indução de tolerância ao déficit hídrico - Pinheiro, Florine Alves de Sousa (2023)
Water deficit negatively affects the physiological aspects of plants, such as stomatal closure and CO2 decrease and, consequently, decline in photosynthetic carbon assimilation. However, currently many techniques for mitigating water deficit in plants have been investigated, such as the use of bioregulators, in order to minimize the damage caused. This work aimed to identify the effects of brassinosteroids on physiological aspects in açaí seedlings (Euterpe oleracea Mart.) in the induction of tolerance to water deficit. The experiment was carried out in a randomized block design in a 2x3 factorial scheme, corresponding to two water conditions (irrigated plants and under water deficit) and three concentrations of brassinosteroids (0, 0,05 and 0,10 μM of 24 - epibrassiolide - EBR), with six replications. Seedlings with 120 days were transplanted into pots containing 14,6 kg of soil. After transplanting, the açaí plants were irrigated once a day, keeping soil moisture close to field capacity for 56 days. After this period, irrigation was gradually suspended in the plants corresponding to the water deficit treatment, until reaching 20% of field capacity. The period under water deficit was up to 18 days, from the suspension of irrigation. The water deficit reduced the gas exchange variables significantly at 12 days, however at 18 days there was a smaller reduction of these variables referring to the concentrations of 0,05 and 0,10 μM of EBR. The application of EBR in açaí plants subjected to water deficit conferred better performance in the concentration of 0,10 μM of EBR in water use efficiency (WEU) as well as chlorophyll, carotenoids and relative water content in plants under deficit. The proline content in plants under water deficit was higher in the concentration of 0,10 μM of EBR. followed by the concentration of 0,05 μM of EBR, while a low level was found without application of BRs. It is concluded that the foliar application of brassinosteroids in young açaí plants under water deficit increases the proline content, the photosynthetic rate, stomatal conductance, transpiration and the efficiencies in water use and carboxylation, in addition to the maximum efficiency of photosystem II and the density of active reaction centers; maintains the concentration of photosynthetic pigments and the relative water content in the leaf, contributing to improve the tolerance of açaí seedlings to water scarcity. The application of brassinosteroids at a concentration of 0,10 μM is more efficient than the application of 0,05 μM of epibrassinolide.